O papel dos conjuntos habitacionais na produção do espaço urbano de Barra do Garças - MT - Ramos, Mágdiel Martins (2015)
This work subscribe to the line of research Planning and Land Management, and addressed the issue of production of urban space of Barra do Garças - MT by the State's actions in the production of housing. In the social division of the city, urban space is a reflection of a state action, which is placed a particular social group within this housing development, thereby generating a stronghold of a certain fraction of the company based on purchasing power. This investigation, as empirical reference the housing of Barra do Garças, that somehow expresses the grouping policy of equal. He intended thereby to show that the State's actions, even contributing to annihilate the housing deficit, it creates a socio-spatial segregation based on the purchasing power of families. This conduct by state power, generated neighborhoods known for social condition of its residents.